Return Migration and Crises in Non-Western Countries
XVII, 237 p. 7 illus., 3 illus. in color.
Keywords: This edited book focuses on the intersection of return migration and crises in non-Western countries. The book explores a wide range of theoretical and methodological perspectives while offering practical insights to address the intricate issues surrounding return migration and crises. The topics covered within this volume include return migration trends, the pivotal roles and contributions of return migrants, the social, psychological, and policy challenges faced by returnees, emerging issues stemming from return migration in their home countries, and the public and formal responses to return migration and the reintegration of returnees, and the roles of crises in these areas. This edited volume brings together diverse perspectives of academic researchers, practitioners, and policymakers on return migration. The book features cases of multiple non-Western countries in Asia (Philippines, China, India), Europe (Lithuania, Turkey, & Ukraine), the Middle East and North Africa (Morocco), and South America and the Caribbean (Mexico, Peru & Dominican Republic). Findings provide a unique opportunity to critically explore current thinking on return migration and investigate the relationship between migration and crisis from varying policy and operational viewpoints. This book, hence, attends to practitioners to develop creative solutions to both global and local policies and practices of return migration management in emerging market countries, which will support and accommodate both their returnees and residents amid challenging times. Jungwon Yeo is an Associate Professor in the School of Public Administration at the University of Central Florida. Her primary research focuses on enhancing attitudes, behaviors, and cognitions of diverse individuals and organizations and their collective decision-making process in critical policy contexts, such as disaster and crisis management, migration, and human security. Additionally, her research explores key topics shaping contemporary discourse in public administration, including accountability, ethics, leadership, and social justice, and their consequential impact on public service provision. Her research experience is demonstrated through refereed publications, national and international conference presentations, and multi-year interdisciplinary research grant awards.